Micronutrient intake and premenstrual syndrome in female collegiate athletes - Pallante, P. I.; Vega, A. C.; Escobar, A.; Hackney, A. C.; Rubin, D. A. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: In non-athletic populations micronutrient consumption is associated with premenstrual syndrome (PMS). PMS can be a debilitating condition for female athletes as it may affect their performance and training. This study investigated potential differences in select micronutrients` intake in female athletes with or without PMS. METHODS: Participants were thirty NCAA Division I eumenorrheic female athletes ages 18-22 years not using oral contraceptives. Participants were classified with or without PMS using the Premenstrual Symptoms Screen tool. Participants completed dietary logs (two weekdays and one weekend day) one week before their projected menstruation. Logs were analyzed for caloric, macronutrient, food sources, and vitamin D, Mg, and Zn intake. Non-parametric independent T-Tests determined differences in the median and Mann-Whitney U tests determined differences in the distribution between groups. RESULTS: 23% of the 30 athletes showed PMS. There were no significant (P>0.22) for all comparisons) differences between groups for daily kilocalories (2150 vs. 2142 kcals), carbohydrates (278 vs. 271g), protein (90 vs. 100.2g), fats (77 vs. 77.2g), grains (224.0 vs. 182.6g), dairy (172.4 vs. 161.0g). vegetables (95.3 vs. 263.1g), or fruits (204.1 vs. 156.5g). A statistical trend (P=0.08) indicated differences in vitamin D intake (39.4 vs. 66.0 IU), but not for Mg (205.0 vs. 173.0 mg), or Zn (11.0 vs. 7.0mg) between groups. CONCLUSIONS: No association was found between Mg, and Zn intake and PMS. However, lower vitamin D intake tended to be associated with presenting PMS in female athletes. Further studies should include vitamin D status to clarify this potential association.